An opportunity to reimagine investment arbitration in Beijing - Mark Feldman (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
This Perspective argues that two global, Beijing-based institutions - the Asian Infrastructure Investment Bank and the International Commercial Dispute Prevention and Settlement Organization - have an opportunity to contribute to the development of a Beijing-based international investment dispute resolution hub.
Keywords: 330